Le Maroc au temps des femmes ? La féminisation des associations locales en question - Yasmine Berriane (L’Année du Maghreb)
In Morocco, reforms and changes are now among priorities on the political agenda. Promoting women's participation in public life is one of those priorities. Through the study of the feminization of local associations in a contained area, this article examines the ensuing socio-political transformations. Our research is actually based on the analysis of the careers of thirty women who have successfully established themselves as community leaders in the suburbs of the city of Casablanca where, not so long ago, local associations were exclusively run by men. The conclusions drawn from this study emphasize the ambivalence of the changes occurring in Morocco today. While the assertion of female community leaders shows a clear break from the traditional distribution of roles between men and women, a detailed analysis of their emergence also shows that their vertical ascent goes through a process of reproduction even reinforcement of certain standards and practices that once contributed to exclude them from the local public sphere.